PERAN KEPALA DAERAH DALAM PENCEGAHAN PERUSAKAN LINGKUNGAN BERDASARKAN UNDANG-UNDANG TENTANG PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP DI KABUPATEN PROBOLINGGO PROVINSI JAWA TIMUR: The Role of Regional Heads in Effort to Prevent to Prevent Environmental Destruction Based on Law Concerning Enviromental Protection and Management in Probolinggo Regency, East Java Province - Agustiani, Rissa Fatikha; Wijiningsih, Ninuk (AMICUS CURIAE, 2024)
In essence, humans and the environment are interconnected. The environment is considered an exploitative factor that causes natural disasters. The government's position in controlling illegal logging is one of the factors in finding a balance between environmental improvement and poverty. The issues discussed in this journal are: The authority and position of the Government of Probolinggo Regency, East Java Province in efforts to protect and manage forests and whether the efforts made by the Government of Probolinggo Regency, East Java Province in carrying out forest protection and management are in accordance with relevant laws and regulations. The type of research used by the author is normative research and statutory research. Based on the essence of the studies and discussions conducted, it can be concluded that (1) forest  cover tenure rights are granted by the district government, such as: restoration, security, and forest preservation, (2) The position of the government and regional governments in forest management is to guarantee forest and land security, forests, (3) The competence of local governments in their efforts to eradicate illegal logging as happened in the area can be prevented. into five categories, mainly under local government announcements as determined by law.